(untitled) ("Temas Sociais" Journal, 2025)
This article presents a brief reflection on grief as a universal and inevitable experience. Based on various models, such as that of Elisabeth Kübler-Ross, this paper aims to be a theoretical contribution to the understanding of the stages of grief in social intervention. It addresses the different types of grief and distinguishes between normal and pathological grief, highlighting the growing relevance of this distinction in social intervention. The way it is experienced varies according to individual and cultural factors, so different risk factors that may be associated with pathological grief are presented with the aim of identifying the needs of the bereaved and providing appropriate support. As we get older, we are more likely to experience bereavement, and the main aim of this article is to promote a better understanding of this process in order to provide more effective and efficient psychosocial support to the older people/bereaved. Keywords: Grief; Theoretical Models; Risk Factors; Social Interventions.